Fluid–structure coupling mechanism and its aerodynamic effect on membrane aerofoils. (13th June 2018) - Serrano-Galiano, Sonia; Sandham, Neil D.; Sandberg, Richard D.
Abstract : Fluid–structure interactions of elastic membrane aerofoils are investigated at Reynolds number $Re=10\, 000$ and low angle of attack. The dynamics of the fluid and membrane coupled system are solved using direct numerical simulation (DNS), where the geometry and boundary conditions were applied using a boundary data immersion method. Although membrane aerofoils improve the aerodynamic performance close to stall conditions compared to rigid aerofoils, it has previously been found that membrane aerofoils show lower aerodynamic efficiency at low angles of attack. This study focuses on the coupling mechanism at an angle of attack of 8 degrees, which is below the stall angle. The dynamic behaviour of the coupled system was characterised via spectral analysis in the wavenumber and frequency domain, which allowed the propagating wave nature of the membrane vibrations and their effect on the surrounding pressure field to be clarified. The membrane vibrations are found to introduce upstream-propagating pressure waves that appear to be responsible for a loss in aerodynamic efficiency compared to a rigid aerofoil. Comparison of two- and three-dimensional results reveals that the three-dimensional flow development causes a decrease in the amplitude of the system fluctuations, but the same coupling mechanism is present.